Meningkatkan Kecepatan Tendangan Lingkar Dalam Dengan Latihan Resistance Band Lying Leg Press Pada Atlet Tarung Derajat Lombok Timur - Jamaludin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The problem in this study is the lack of kicking speed, especially kicks in the inner circle because the athlete's legs are not trained in a structured and measured way when determining the training load for fighting athletes. In addition, the lack of discipline from athletes that affects the lack of speed in kicking. The purpose of this study was to determine whether or not there was an effect of the Resistance Band Lying Leg Press exercise on the speed of the inner circle kick of the fighting athlete at the Masbagik training center in East Lombok. This research is an experimental study with data collection techniques using an action test. The subjects of this study were all fighting athletes at the Masbagik training center, East Lombok. The inner circle kick speed test used is a test of basic martial technique skills. The subjects of the study were combat athletes at the Masbagik training center in East Lombok, with 11 athletes. The data analysis technique used t test with SPSS version ”21. From the results of data analysis, it can be concluded that the alternative hypothesis is accepted and the null hypothesis is rejected. These results can be interpreted that there is an effect of training using the Resistance Band Lying Leg Press on the speed of the inner circle kick in fighting athletes at the Masbagek training center, East Lombok in 2022.